Disaster Preparedness and First Aid Response: The Role of Emergency Nurses - Olaolorunpo Olorunfemi; Olufunke Beatrice Adesunloye (Archives of Medicine and Health Sciences)
Emergency nurses are pivotal in disaster preparedness and first aid response, being the first healthcare providers on the scene during emergencies. Their ability to assess situations swiftly, triage patients effectively, and collaborate with other professionals ensures timely and efficient care. They also contribute significantly to disaster preparedness by participating in drills and training, and by assisting in developing and implementing emergency response plans. Natural catastrophes harmed about 2 billion people worldwide between 2008 and 2018. According to the World Health Organization, countries and governments must always have catastrophe preparations and emergency health experts on hand. This review article aimed to examine the current level of disaster preparedness among nurses, to analyze some of the factors influencing nurses’ emergency preparedness and to define the roles of emergency nurses in both rapid first aid deployment and long-term disaster impact reduction. The data for this review paper are from published studies. Electronic databases of MEDLINE, PubMed, and Google Scholar were searched using the keywords: disaster preparedness, first aid response, emergency nurses, roles of nurses, and disaster response, and literature were retrieved and screened for eligibility. The date limit considered in the literature search was from 2018 to 2024 to capture only the variables identified in the study. The review revealed four issues which are (1) the Haddon Matrix Model, (2) current level of disaster preparedness among nurses, (3) roles of emergency nurses in disaster management, and (4) analyzing emergency preparedness and first aid impact of nurses in disasters. In conclusion, addressing these issues through targeted training, resource allocation, and policy implementation can enhance the overall preparedness of nurses in responding to disasters and improving outcomes for those affected. Ensuring that nurses are well-prepared, adequately trained, and equipped with the necessary resources, healthcare systems can better mitigate the impact of disasters and provide timely and effective care to those in need. This not only benefits the individuals directly affected by disasters but also strengthens the resilience of communities and healthcare systems as a whole.